Issues in religion and education whose religion? - Beaman, Lori G. 1963-; Van Arragon, Leo (Leiden [u.a.] Brill, 2015)
Literaturangaben
Includes bibliographical references and index
Keywords: Religion in the public schools -- Cross-cultural studies -- Congresses; Church and education -- Cross-cultural studies -- Congresses